TREN PENELITIAN TENTANG OTOMASI DAN PUSTAKAWAN PADA PUBLIKASI TERINDEKS SCOPUS TAHUN 1997-2022 - Prasetyo Adi (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2022)
Automation technology or machines with artificial intelligence are now doing the work done by workers. The librarian's core tasks should be replaced by automata to empower librarians to do other, more productive jobs. This study aims to observe how much use of machines with AI technology in library services, especially manual work. The study took samples from the Scopus website. Data is collected by entering keywords (TITLE-ABS-KEY (“automation”)) AND (“librarian”) on the Scopus search page. It was found around 940 population of papers and about 923 papers were taken for analysis. Data were analyzed by bibliometrics. The results show that AI is becoming one of the trending topics in research for writers. This is because AI is the brain to run automation itself, so a lot of research is needed to examine the development of the use of AI. The results also show where the keywords that are widely used and have a high level of relevance and development according to the field of study, namely automation, paper, and information. This shows that the keywords about automation have been well developed and are very relevant to the field of study of the paper as a sample.